Evaluasi Kunjungan Balita ke Posyandu di Wilayah Kerja Puskesmas Mamboro - Fatmawati; Rajindra; Zhanaz Tasya (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Toddler visits to integrated health posts (Posyandu) are essential for monitoring growth and development, preventing nutritional problems, and strengthening community-based primary health services. However, the coverage of toddler visits in the working area of Mamboro Health Centre remains fluctuating and has not fully reached the expected target. This study aimed to evaluate the implementation of the toddler visit program to Posyandu by examining structural, process, and outcome aspects as well as behavioral factors influencing mothers’ attendance. This qualitative research used a descriptive case study design. Data were collected through in-depth interviews, observation, and documentation involving mothers of toddlers as main informants, cadres and health workers as key informants, and husbands and village officials as triangulation informants. Data were analyzed inductively through data reduction, data display, and conclusion drawing. The findings showed that the program had generally been implemented well. Cadres and health workers were available, standard operating procedures were understood, and cadre training had been conducted. Posyandu activities followed the five-table service flow, although health education and cross-sector coordination still required strengthening. Outcome indicators such as D/S and N/D remained fluctuating because attendance was not yet stable. The study concludes that toddler visit activities at Posyandu have been implemented fairly well, but routine attendance, growth monitoring coverage, family support, and community participation need further improvement.